2014
DOI: 10.1002/ijc.28946
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA in healthy individuals, noncancerous disease and strong prognostic value in colorectal cancer

Abstract: The purpose was to investigate total cell-free DNA (cfDNA) in colorectal cancer (CRC) patients during treatment with secondline chemotherapy and in healthy controls and patients with different comorbidities. Patient treated with second-line irinotecan for metastatic CRC (n 5 100), a cohort of healthy controls with and without comorbidity (n 5 70 and 100, respectively) were included. cfDNA was quantified by an in-house developed quantitative polymerase chain reaction from plasma samples drawn prior to the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 18 publications
8
78
0
1
Order By: Relevance
“…Several reports have already described the potential impact of ccfDNA on the prognosis of patient outcome in terms of either OS or progression-free survival (6,9,28,29). Most of these previous publications were oriented to analyze the correlation between an increase in the total level of ccfDNA with a decrease in PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have already described the potential impact of ccfDNA on the prognosis of patient outcome in terms of either OS or progression-free survival (6,9,28,29). Most of these previous publications were oriented to analyze the correlation between an increase in the total level of ccfDNA with a decrease in PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells release ccfDNA, which exhibits the genetic and epigenetic alterations of the tumor of origin (4). The clinical significance of tumor-derived ccfDNA released in the blood of patients with colorectal cancer has already been investigated as a prognostic tool in previous studies using various technologic approaches (5)(6)(7)(8)(9). In a recent large meta-analysis, a high correlation between ccfDNA concentration and mCRC patient survival was observed, revealing that patients with relatively low levels of ccfDNA lived significantly longer than patients with higher levels (6).…”
Section: Introductionmentioning
confidence: 99%
“…Identical laboratory methods were used, and the analyses showed similar baseline levels in all cohorts of mCRC patients [32,33,[54][55][56][57][58][59]. Furthermore, analysis of samples from a large normal cohort enabled definition of an upper normal limit [57]. In addition, the levels of cfDNA seem stable between different cohorts of CRC patients, (whereas some differences seem to exist between different tumor types as illustrated in the data from Perkins et al [64]).…”
Section: Clinical Utility Of Total Cell-free Dnamentioning
confidence: 95%
“…Although the potential that lies in detection and measurement of the tumor-specific DNA has been established, the clinical value of total cfDNA quantification is still being debated. Only few studies take the total levels of cfDNA into consideration as a picture of the overall complex biology, but recently a series of studies reported a clear correlation between total cfDNA levels and mutated DNA [45,[54][55][56][57][58][59][60][61][62][63].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation